2020
DOI: 10.1016/j.diabres.2020.108307
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus lockdown effect on type 1 diabetes management οn children wearing insulin pump equipped with continuous glucose monitoring system

Abstract: On the 10th of March, Greece imposed the closure of schools and universities and a full lockdown a few days later in order to counter the spread of the coronavirus outbreak.Our aim was to monitor the effect of the coronavirus lockdown in diabetes management in children with Type 1 Diabetes Mellitus (T1DM) wearing insulin pump equipped with continuous glucose monitoring system. Methods:In 34 children with T1DM on Medtronic 640G insulin pump equipped with the Enlite Sensor uploaded CareLink data were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 18 publications
(22 reference statements)
8
61
0
2
Order By: Relevance
“…In this study data of 3-weeks before and after lockdown were compared and no significant difference in insulin TDD and TIR values was demonstrated. The %CV values significantly decreased, but they were reported to be above 36% (53). During the first 2-weeks lockdown period, as compared to the 2-weeks previous, higher TIR values and lower TAR values were demonstrated in Italian pre-school and school T1D children using CGM and semi-automated insulin delivery systems, while TBR was unchanged.…”
Section: Discussionmentioning
confidence: 86%
“…In this study data of 3-weeks before and after lockdown were compared and no significant difference in insulin TDD and TIR values was demonstrated. The %CV values significantly decreased, but they were reported to be above 36% (53). During the first 2-weeks lockdown period, as compared to the 2-weeks previous, higher TIR values and lower TAR values were demonstrated in Italian pre-school and school T1D children using CGM and semi-automated insulin delivery systems, while TBR was unchanged.…”
Section: Discussionmentioning
confidence: 86%
“…A study involving type 1 DM patients undergoing continuous glucose monitoring (CGM) reported a significantly longer time at target blood sugar levels (70–180 mg/dl) over a 14-day lockdown period compared to pre-lockdown, although no difference was detected in time remaining hypoglycemic [ 15 ]. In a similar study of type 1 DM patients followed-up with CGM, no statistically significant difference was found between pre-lockdown and post-lockdown glucose parameters, although a significant difference was determined between breakfast and dinner [ 16 ]. These two studies were consistent with the present research in terms of, contrary to expectation, the lockdown period having no adverse impact on glucose parameters, and in terms on increase in hypoglycemia being observed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the previous study which reported change in routine care of the people suffering from chronic diseases [ 5 ]. Similarly, it was reported that glycemic control of diabetic patients was affected in the lockdown period [ 6 ]. Children suffering from gastrointestinal disorders also severely affected due to the lockdown [ 7 ].…”
Section: Discussionmentioning
confidence: 99%